Myths and misunderstandings in white-collar crime - Baer, Miriam H. (Cambridge University Press, 2023)
"For years, commentators have complained that white-collar crime is both overcriminalized and underenforced. This book transcends that debate and argues that white-collar crime's weaknesses rest on how we make its laws, how we enforce them, and how we talk about enforcing them"--